Aeroponics growing vertical - Gurley, Thomas W. (Thomas Wood) (Boca Raton, FL : CRC Press, 2020)
Aeroponics: Growing Vertical covers aspects of the emerging technology, aeroponics, which is a sister to hydroponics, involving state-of-the-art controlled environment agriculture. The book begins with an introduction of aeroponics followed by a summary of peer-reviewed technical literature conducted over 50 years involving various aspects of aeroponics. It covers the science and all the patent literature since 2001 to give the reader a comprehensive view of the innovations related to aeroponics. This book is a useful reference for people interested in learning about how aeroponics works. This book is for novices as well as scientists interested in research activities conducted in countries around the world as well as work in using aeroponics in outer space. Designed for the user interested in research conducted in the past, this a helpful resource for those in the next generation of profitable agricultural endeavors. Features: Comprehensive resource presenting key aspects of aeroponics Focus on areas of aeroponics including its history, science, innovations, business, and practice Provides a complete overview of the intellectual property associated with aeroponics Presents a broad overview of research using aeroponic systems across the globe Features information on key start-up businesses and activities that drive this technology Thomas Gurley earned aBA in chemistry from Houghton College and a PhD in analytical chemistry from Case Western Reserve University and has 40 years industrial chemistry experience with companies including Goodyear, Abbott Labs, and his consulting company, Manning Wood LLC. He holds two Fulbright scholarships to Ukraine and Uganda. He is currently R&D Director for Aero Development Corporation, a manufacturer of aeroponic commercial growing systems. He conducts research in aeroponics as an adjunct professor at Charleston Southern University in South Carolina.
OCLC-licensed vendor bibliographic record.
Keywords: Plant growing media, Artificial; Hydroponics; SCIENCE / Life Sciences / Botany; SCIENCE / Life Sciences / General; TECHNOLOGY / Agriculture / General